Modulation masking phenomenon for masking signals of different spectral and statistical properties - Dariusz Kutzner (Archives of Acoustics, 2014)
Modulation masking effect for modulation maskers of different spectral and statistical properties was investigated in this study. Three noisebands centred at 16 Hz were used as modulation maskers, namely: 1) 32-Hz wide Gaussian noise (GN 32 Hz); 2) 32-Hz wide lownoise noise (LNN 32 Hz) and 3) 4-Hz wide low-noise noise (LNN 4 Hz). The GN 32 Hz and LNN 32 Hz were characterized by the same power spectrum density and different probability density functions. Conversely, the LNN 32 Hz and LNN 4 Hz had the same probability density functions, but different power spectrum densities. The root mean square of the modulation maskers was normalized to 0.2. During the measurements audibility of a sinusoidal probe modulation presented simultaneously with the modulation maskers was investigated by means of the 3AFC adaptive procedure with a 3-down/1-up decision rule. The results of the experiment indicated that modulation masking was mainly determined by power density spectrum of the modulation masker, however, due to peripheral compression, temporal (statistical) properties of the masker might have played also some role in the modulation masking.